Visualization of the Expression of HMGN Nucleosomal Binding Proteins in the Developing Mouse Embryo and in Adult Mouse Tissues - Furusawa, Takashi (2009)
Visualization of the expression pattern of specific proteins during development and in adult tissues provides important clues as to their possible role in various cellular processes. Mouse is the organism of choice for obtaining information on gene expression patterns in higher eukaryotes. This chapter describes the protocols we utilized to visualize Hmgn transcripts and HMGN proteins in mouse tissues. HMGN are chromatin-binding proteins that affect chromatin structure and function and play a role in cellular differentiation.